Cultivating Learner Autonomy in Arabic Grammar: A Root Cause Analysis And Scaffolding Strategy Madrasah Diniyah Students - Abdur Rahman Frima; Moh. Khasairi; Imam Asrori; Wildan Agus Wicaksono (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
The primary objective of this study is to address the persistent mastery gap in Nahwu learning among non residential students at Madrasah Diniyah Ula Hasanul Huda Tajinan. Utilizing a descriptive qualitative design focused on a rigorous needs analysis framework, the research identifies that the suboptimal level of self directed learning is fundamentally driven by a lack of institutional supervision and the abstract complexity of Arabic grammar. The empirical investigation, mapped through a root cause analysis, reveals that environmental distractions and temporal constraints significantly exacerbate cognitive load and syntactic anxiety. To mitigate these systemic challenges, the study proposes the implementation of the Nahwu Tutor application as a digital scaffolding mechanism. Results indicate that integrating structured modules and gamification elements effectively restores academic motivation and provides the necessary pedagogical fluidity for students in informal settings. The research concludes that the application serves as a vital pedagogical anchor that bridges the spatial divide between the madrasah and the home. Ultimately, this methodological synthesis provides a grounded foundation for the digital transformation of religious education, ensuring that technological interventions directly address the socio environmental variables of modern learners.